Wearable Devices Components for High Jump Sport: An Overview - Roslan, Muhammad Faris; Ahmad, Afandi (International Journal of Integrated Engineering, 2020)
Wearable devices like FitBit, Garmin and Amazfit smartwatch have become popular in recent years. Athlete like swimmers and runners mostly use smartwatch to track speed of the swim or run using embedded global positioning system (GPS) sensor in the wearable devices. Unfortunately, high jump sports still on the old style in tracking the movement of the jump by using vision system. Thus, this paper presents an overview on related work, existing methods and developments on the area of wearable sensor for high jump sports. The analysis of high jump sports related works in terms of main injury and parameters to prevent the injury are being analysed. The used of biosensors in recent wearable devices has been also reviewed in term of the types and issues of sensor that need to implements in the wearable device. Other than that, the processing methods that contains Internet of Thing (IoT) gateway device, network transmission and real-time monitoring system (RtMS) are proposed to develop a complete wearable device. Finally, the main injury parameters of the high jump sports and sensors related to the parameter has been reviewed and an overall idea of processing method RtMS has been summarised.